MODELS THE COMPETITIVE UNIVERSITY GOVERNANCE : A CASE STUDY AT ISLAMIC MUHAMMADIYAH UNIVERSITY OF EAST BORNEO: Models the Competitive University Governance - Rahayu, Anik Puji; Subagiyo, Lambang; Warda, Khusnul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
Good university governance is expected to increase the public image which leads to promoting credibility and public participation in the role of the university. Some roles expected by society from universities are to give qualified education, develop research, transfer knowledge, culture, and technology and promote the economy within society. Continuous improvement enables universities to always increase their quality to become highly competitive. This study aims to develop strategic models for competitive university governance at the Muhammadiyah Islamic University of East Borneo. The qualitative approach with a Case study type was used in this research. The data were collected through depth-interview, participation observation, and document study. The findings concerning the strategic model of the competitive university governance characteristics were interrelated, as follows: 1). Internal Quality Factors: the Personal Character Building by developing caring spirituality, awareness, and total action in which all came from the conscience (honesty, responsibility, visionary, discipline, cooperation, just and caring. 2) External Quality Factors: the Quality Culture and IT-based organization by developing vision, mission, and organizational character, excellent leadership, stakeholder, Good University Governance management, the national standard university, Quality assurance, and creative innovation. 3) Outcome: Achieving the University Index, achieving the university roles, the graduate's competence, and consumer satisfaction, hence achieving a competitive university.